HARMONI VOKAL ALAMI DALAM PADUAN SUARA MUSIK GEREJA DI GPIB JEMAAT PENABUR SURAKARTA - Agus Budi Handoko (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2012)
This article is the result analyze of research the potency of chorusmembers inmaking a natural vocal harmony at Church,which is a harmony that is not emerging or came fromthe concept of harmonic theory ofwesternartmusic. The authormakesseveral questions in the problemstatements related to: (1) Skill development of producing natural vocal harmony. (2) Theresult of natural vocal harmony. (3) The use of thatmusical potency in their life. This research uses qualitative approach.Concepts that are used in the data collections are: phenomenological, ethnographic and concept harmony ofmusic.Results ofthe research are: (1) Potency development of producing natural vocal harmonywhich are triggered by two things, namely:background of Church and background of their culture. (2) Form of natural harmony is generally almost similar to theconventional harmony, but if they are examined carefully, then there are differences between them, namely: the process,characters’ arrangement for each kind of voice, and howthey present it. (3) Their potency could be used to as an effective toolfor praising the Lord, supporting the religious service, and get themcloser toGod.Keywords:Harmony,Choir, ChurchMusic